Benign epilepsy with centrotemporal spikes: Correlating spike frequency and neuropsychology. (19th September 2018) - Tacke, Moritz; Rupp, Nina; Gerstl, Lucia; Heinen, Florian; Vill, Katharina; Bonfert, Michaela; Neubauer, Bernd Axel; Bast, Thomas; Borggraefe, Ingo; ,
Abstract : Objectives: Neuropsychological sequelae are a feature of benign epilepsy with centrotemporal spikes (BECTS) in children. A correlation between the frequency of interictal EEG discharges and the cognitive as well as behavioral profile of the patients has been suspected but not proven. Materials and methods: Children with BECTS that had not yet been treated were included into a randomized controlled trial. In the initial visit, EEGs were recorded. The frequency of interictal discharges was quantified. Correlations between the discharge frequency and the performance in a neuropsychological test battery were examined. Results: The cognitive test results were within or slightly above normal range (Culture‐free intelligence test: 99.4%‐confidence interval [CI]: [50.3, 59.9], test standardized to a population mean of 50). Parent‐reported behavioral abnormalities were statistically significantly increased (CBCL total score CI: [51.9, 61.9], population mean as above). Correlations between the frequency of interictal epileptic discharges and the test results could not be identified (lowest encountered P ‐value: 0.034, not significant after correction for multiple testing). Conclusion: The data do not support the hypothesis that the frequency of the interictal EEG discharges influences the neurocognitive performance or behavioral parameters of children with BECTS.